Prevalence of competitor and parasitic moulds during milky and white button mushroom cultivation in Haryana - Singh, Ajay; Sharma, V P; Kumar, Satish; Varshney, Anjum; Singh, Rajinder (Mushroom Research, 2015)
Please see the full text